(untitled) (Biological Sciences - PJSIR, 2002)
Effect of different soaking and cooking method s on some ph ysical characteristics, phytic acid content and protein digestibility of red kidney beans is reported. Soaking of kidney bean s in 4% acetic acid sol ution gave ri se to lower hydration capacity, hydration index, swelling capacity and cooking time than soaking in tap water. Phytic acid contents of red kidney beans were reduced to various extents on soaking in different solutions at 30°C and 100°C. However, soaking in acetic acid solution with or without sodium chloride was the most efficient method for reducing phytic acid. Phytic acid was further reduced on cooking by different ways. Cooking in a pressure cooker caused maximum reduction in phytic acid contents. Ordinary and microwa ve cooking also showed pronounced effect on reduction of phytic acid. Reduction in the level of phytic acid was not found respon sible for improving the protein digestibility of red kidney bean s.